2007
DOI: 10.1016/j.beth.2006.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing and Externalizing Subtypes in Female Sexual Assault Survivors: Implications for the Understanding of Complex PTSD

Abstract: This study replicated and extended findings of internalizing and externalizing subtypes of posttraumatic psychopathology (Miller, M. W., Greif, J. L., & Smith, A. A. (2003). Multidimensional Personality Questionnaire profiles of veterans with traumatic combat exposure: Internalizing and externalizing subtypes. Psychological Assessment, 15, 205-215; Miller, M. W., Kaloupek, D. G., Dillon, A. L., & Keane, T.M. (2004). Externalizing and internalizing subtypes of combat-related PTSD: A replication and extension u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
182
3
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(222 citation statements)
references
References 77 publications
34
182
3
3
Order By: Relevance
“…These findings, and those reviewed previously, suggest that PTSD may arise as a function of latent liabilities towards either internalizing or externalizing psychopathology. This proposition is consistent also with recent studies of personality-based subtypes of PTSD, which have shown that many adults with PTSD exhibit a predominantly externalizing pattern of comorbidity characterized by problems in the domain of impulse-control, antisociality, and substance abuse (Miller, Greif, & Smith, 2003;Miller, Kaloupek, Dillon, & Keane, 2004;Miller & Resick, 2007).…”
Section: Comorbidity Studies and The Location Of Posttraumatic Stresssupporting
confidence: 86%
“…These findings, and those reviewed previously, suggest that PTSD may arise as a function of latent liabilities towards either internalizing or externalizing psychopathology. This proposition is consistent also with recent studies of personality-based subtypes of PTSD, which have shown that many adults with PTSD exhibit a predominantly externalizing pattern of comorbidity characterized by problems in the domain of impulse-control, antisociality, and substance abuse (Miller, Greif, & Smith, 2003;Miller, Kaloupek, Dillon, & Keane, 2004;Miller & Resick, 2007).…”
Section: Comorbidity Studies and The Location Of Posttraumatic Stresssupporting
confidence: 86%
“…la muestra clínica, aun habiendo sido muy amplia (mucho mayor que en los estudios previos: por ejemplo, crespo y gómez, 2015 o Foa et al, 2016), ha estado limitada a mujeres víctimas de violencia de género. aun siendo estos grupos en los que es más frecuente el tept y los que mayor demanda terapéutica generan en nuestro medio en relación con este cuadro clínico (Miller y Resick, 2007), convendría Enrique Echeburúa, Pedro J. Amor, Belén Sarasua, Irene Zubizarreta, Francisco Pablo Holgado-Tello, José Manuel Muñoz.…”
Section: Conclusionesunclassified
“…VA Author Manuscript on internalizing or externalizing behavior (see, e.g., Forbes et al, 2010;Miller, Greif, & Smith, 2003;Miller, Kaloupek, Dillon, & Keane, 2004;Miller & Resick, 2007). While these studies have supported the internalizing/externalizing distinction as a useful heuristic for studying the structure of posttraumatic psychopathology, they are limited by a reliance on cluster-analytic models which are not optimal for examining higher order factor structure of psychopathology thought to be dimensional (Miller, Fogler, Wolf, Kaloupek, & Keane, 2008).…”
Section: Va Author Manuscriptmentioning
confidence: 99%
“…other studies that have used cluster-analytic methods to classify participants as belonging to either an "internalizing," "externalizing," or "low pathology" subtypes of PTSD (e.g., Miller et al, 2004;Miller & Resick, 2007). It would be helpful in future research to compare the utility of these approaches as they relate to relevant outcomes among individuals with PTSD.…”
Section: Va Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation